Bacterial Accumulation on Triclosan-Coated and Silk Sutures After Dental Implant Surgery - A Etemadi; T Bitaraf; A Amini; M Goudarzi; N Nadafpour (Islamic Azad University, 2019)
Background and Aim: The risk of surgical site infection may depend on bacterial attachment and physical and chemical properties of suture materials. This study aimed to evaluate bacterial accumulation on triclosan-coated (Vicryl Plus) and silk sutures placed at different distances from Vicryl Plus after dental implant surgery. Materials and Methods: In this randomized controlled trial, 20 patients who required dental implants were included. Their surgical sites were large enough to include at least four sutures. The surgical site was sutured first with Vicryl Plus and then with three silk sutures placed at 3, 6, and 9 mm distances from Vicryl Plus. Sutures were removed 7 days after surgery, and the samples were placed in microbiological cultures specific to Enterococci and Escherichia coli (E. coli). Subsequently, the numbers of colony-forming units (CFUs) and bacterial growth rates were evaluated. Kruskal-Wallis and Mann-Whitney U tests were used for statistical analysis. Results: There were no significant differences in the number of CFUs and growth rates of microorganisms isolated from triclosan-coated and silk sutures 7 days postoperatively (P>0.05). Conclusion: Triclosan-coated sutures have no benefits over silk sutures placed at different distances from Vicryl Plus.